Urine Concentration Does Not Affect Biochemical Testing for Non-adherence. Issue 3 (10th December 2020) - Burns, A D; Alghamadi, R; Iqbal, A; Davies, T; Lane, D; Patel, P; Gupta, P
Abstract: Hypertension is one of the most important modifiable risk factor causing cardiovascular disease. Unfortunately, non-adherence to antihypertensive medications is frequently observed in hypertensive patients and can lead to an increase in morbidity and mortality. Until recently, there was no robust clinical method to objectively diagnose non-adherence. Recently, the detection of medications in urine or blood by mass spectrometry techniques such as liquid chromatography-tandem mass spectrometry (LC–MS-MS) has been accepted as the diagnostic method of choice for the detection of non-adherence. Despite this, it is unclear whether the concentration of urine can affect the detection of medications in urine. Therefore, this study aimed to assess the effect of urine concentration on detection of antihypertensive medications by LC–MS-MS in which urine creatinine is used as an independent marker of urine concentration. Biochemical adherence results for 22 different medications (1, 709 prescriptions) in 463 different subjects were converted to an adherence score. The adherence score was defined as the ratio of the total number of subjects in which the drug was detected to the total number of subjects to whom the drug was prescribed. The adherence scores for each medication were correlated with urine creatinine concentration for each medication. Non-adherence was observed in 47.1% of samples with a mean urine creatinine concentration of these samples of 9.4 ± 7.1 mmol/L. There was no significant difference between the urine creatinine concentrations in the detected vs non-detected groups for each of the 22 medications. Furthermore, there are no differences in adherence scores across the urine creatinine concentration. This is the first study to demonstrate that urine creatinine concentration does not affect the results of the adherence screening by LC–MS-MS.